Using Feminism Approach To Comparison The Main Characters The Queen in The Novel Snow White and The Seven Dwarfs - Ni Putu Wiwik Krismayani (STKIP AGAMA HINDU SINGARAJA, 2023)
This study aims to find out the similarities and differences of